Threshold concepts in higher education: a synthesis of the literature relating to measurement of threshold crossing. Issue 1 (2nd January 2018) - Nicola-Richmond, Kelli; Pépin, Geneviève; Larkin, Helen; Taylor, Charlotte
ABSTRACT: In relation to teaching and learning approaches that improve student learning outcomes, threshold concepts have generated substantial interest in higher education. They have been described as 'portals' that lead to a transformed way of understanding or thinking, enabling learners to progress, and have been enthusiastically adopted to inform teaching approaches and curriculum design. A growing body of literature has critiqued the relevance and applicability of the threshold concept theory and identified threshold concepts relevant to specific disciplines. More recent research has identified how students cross these thresholds and provided measures of the successful acquisition of threshold concepts. This literature synthesis critiques existing evidence on threshold crossing and acquisition to provide a succinct and informative overview of the outcomes to date. Key questions relevant to educators and researchers investigating whether students acquire the threshold concepts associated with their teaching, arose from the literature synthesis. These were: whether or not threshold crossing can be measured; how variation in student learning can be addressed during measurement; tools that can be used for measuring threshold crossing; whether the way units or concepts are taught should alter prior to measurement, and the challenges and limitations of measuring threshold crossing.